Citizens’ evaluations of campaign pledges fulfillment in six countries - François Pétry; Robert Thomson; Elin Naurin; Belchior, Ana Maria; Heinz Brandenburg; Dominic Duval; Justin Leinaweaver; Henrik Oscarsson (ECPR General Conference, 2017)
Relying on recent national election surveys, we compare citizens’ evaluations of the fulfillment of 36 specific campaign pledges in Canada, Great Britain, Ireland, Portugal, Sweden and the United-States. We find that citizens’ evaluations are accurate (they match actual government performance) 62% of the time. In order to arrive at their verdicts as to whether specific pledges are fulfilled or not, citizens often use heuristic shortcuts such as party ID and political trust. We show that the use of these heuristic shortcuts is a double edged sword. Why they help citizens to make accurate evaluations in some circumstances, under different circumstances the same shortcuts mislead citizens into making inaccurate evaluations. We also find that the accuracy of evaluations increases with an increase in the level of political knowledge of respondents.